Traits Explaining Durum Wheat (Triticum turgidum L. spp. Durum) Yield in Dry Chilean Mediterranean Environments - González-Ribot, Gerlitt; Opazo, Marcela; Silva, Paola; Acevedo, Edmundo (Frontiers in Plant Science, 2017)
Yield under water stress (YS) is used as the main criterion in the selection of wheat varieties for dry Mediterranean environments. It has been proposed that selection of genotypes using YS assisted by morphological and physiological traits associated with YS, is more efficient in selecting high yielding genotypes for dry environments. A study was carried out at the Antumapu Experiment Station of the University of Chile, located in Santiago, Chile (33°40’S and 70° 38’ W). The objective was to evaluate the extent to which morpho physiological traits could explain YS. For this purpose, grain yield and yield components of 185 durum wheat genotypes from ICARDA (International Center for Agricultural Research in the Dry Areas) and INIA (Chilean National Institute for Agricultural research) were evaluated along with seed size and weight, days to heading (DH), glaucousness (GLAU), plant height (PH) and 13C discrimination (∆). The design was an -lattice with two replications, the genotypes were grown in two different water conditions (high and low irrigation) during two seasons (2011-2012/2012-2013). Grain weight (GW) was the only yield component with high H associated with YS, but it was not associated with yield under high irrigation (YI). The combination of YI with DH+GLAU+PH+∆+GW obtained in LI environments explained a greater fraction of YS (38%) across years; these traits had lower genotype x environment interaction than YS, they also explained a higher proportion of yield under drought than YI. None of the traits studied could replace YS in selections for grain yield It is concluded that these traits could aid in the selection of durum wheat subject to water stress, particularly in early generations.